Three thieves. Book 6, The dark island - Chantler, Scott (Chantler, Scott. Three thieves, 2016)
In this thrilling sixth installment of Scott Chantler's popular Three Thieves graphic novel series, the separate adventures of twins Dessa and Jared play out simultaneously and seem poised to intersect as the book ends. Dessa, along with Topper and Fisk, has managed a daring landing onto the flying island of Astaroth, where she hopes to find her long-lost brother. Instead, they discover a bizarre world where three children are being held by a mysterious and rarely seen man they call the Toymaker. Certain the Toymaker is Greyfalcon, Jared's kidnapper, Dessa is determined to track him down and confront him about her brother's location. Meanwhile, Captain Drake has unintentionally stumbled upon Jared himself and decides to hold the boy as bait to lure Dessa to him. But as he learns from Jared the particulars about the boy's abduction nine years ago, Drake is troubled. Why would such powerful people want to abduct a small peasant boy? The answer to that question is about to shock Drake--and Jared!